2015
DOI: 10.1111/josh.12261
|View full text |Cite
|
Sign up to set email alerts
|

School Staff Perspectives on the Challenges and Solutions to Working With Court‐Involved Students

Abstract: Teachers and school staff can play a role in the educational well-being of court-involved youth. However, they need trauma-specific knowledge and resources to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Another major finding is external problems that hinder ability to thrive. Similar to other studies focusing on students in both public (Overstreet & Mathews, 2011;Smithgall et al, 2013;Vidourek et al, 2016) and RT school settings (Crosby et al, 2015;Day et al, 2015), students reported experiencing stress before entering the classroom due to overwhelming socioemotional histories and peer or familial concerns. Students may become consumed by personal dilemmas that may prohibit school performance and attendance, and they are unable to focus on lessons when they are truant.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Another major finding is external problems that hinder ability to thrive. Similar to other studies focusing on students in both public (Overstreet & Mathews, 2011;Smithgall et al, 2013;Vidourek et al, 2016) and RT school settings (Crosby et al, 2015;Day et al, 2015), students reported experiencing stress before entering the classroom due to overwhelming socioemotional histories and peer or familial concerns. Students may become consumed by personal dilemmas that may prohibit school performance and attendance, and they are unable to focus on lessons when they are truant.…”
Section: Discussionsupporting
confidence: 65%
“…Educational opportunities vary greatly in RT settings, from off-campus, public school partnerships in the local community to educational services offered on-site at the RT facility. Although traumatic experiences can affect students in public school environments (Overstreet & Mathews, 2011;Smithgall, Cusick, & Griffin, 2013;Vidourek, King, & Merianos, 2016), youths in RT school settings may have unique trauma-related issues (Crosby, Day, Baroni, & Somers, 2015;Day et al, 2015). This article is restricted to understanding the educational experiences of RT youths in educational programs offered on-site at an RT facility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They should also abide by six main principles: Safety; Trustworthiness and Transparency; Peer Support; Collaboration and Mutuality; Empowerment, Voice and Choice; and Cultural, Historical, and Gender Issues. Research has also shown the efficacy of trauma-informed practices in various child-serving systems, including schools (Crosby, Day, Baroni, & Somers, 2015;Day et al, 2015;Penner & Wallin, 2012), mental health youth residential programs (Hummer, Dollard, Robst, & Armstrong, 2010), child welfare (Conradi et al, 2011;Greeson et al, 2011;Griffin et al, 2011;Ko et al, 2008;Kramer, Sigel, Conners-Burrow, Savary, & Tempel, 2012), and juvenile probation (Maschi & Schwalbe, 2012). Comprehensive efforts to include trauma-informed approaches for all who serve potentially traumatized youth is recommended by several major mental health and child-focused organizations, including SAMHSA and the National Child Traumatic Stress Network.…”
Section: Youth Trauma and The Trauma-informed Approachmentioning
confidence: 99%
“…Comprehensive efforts to include trauma-informed approaches for all who serve potentially traumatized youth is recommended by several major mental health and child-focused organizations, including SAMHSA and the National Child Traumatic Stress Network. Research has also shown the efficacy of trauma-informed practices in various child-serving systems, including schools (Crosby, Day, Baroni, & Somers, 2015;Day et al, 2015;Penner & Wallin, 2012), mental health youth residential programs (Hummer, Dollard, Robst, & Armstrong, 2010), child welfare (Conradi et al, 2011;Greeson et al, 2011;Griffin et al, 2011;Ko et al, 2008;Kramer, Sigel, Conners-Burrow, Savary, & Tempel, 2012), and juvenile probation (Maschi & Schwalbe, 2012). Overall, the purpose of the juvenile justice system is to address delinquent youth as a vulnerable population, provide for the welfare of child offenders, and to advocate for least restrictive treatment environments (Dewey & Gottlieb, 2011).…”
Section: Youth Trauma and The Trauma-informed Approachmentioning
confidence: 99%